ANALISIS KOMPARASI PERHITUNGAN VOLUME PEKERJAAN STRUKTUR BERDASARKAN METODE SPMI DAN BIM - Andre Setiawan; Ferdinand Fassa; Nicolas Hasiando Kusuma (LPPM Universitas Abdurrab, 2022)
QTO (Quantity Take Off) is a measurement for calculating the volume of the entire building in detail. QTO calculation has 2 (two) methods, namely the manual calculation method using the SMPI (Standard Metode Pengukuran Indonesia) and the digital calculation method using BIM (Building Information Modeling). The BIM that used in the calculation of this research is Autodesk Revit. Both methods have their respective advantages, disadvantages, and have the potential to produce different volume calculation results. Therefore, both methods are used in this research and the results has been compared. The results of the total volume be written into a construction document called the BQ (Bill of Quantity). BQ generate calculations from both BIM (Revit) and manual calculations (SMPI). Difference in calculation results between manual calculation (SMPI) and BIM (Revit) calculation for rebar is 0,49%; concrete is 0,14%; while formwork is 0,07%. This indicates that the manual calculation method and the BIM calculation method (Revit) provide approximately same and accurate results. The largest difference in volume calculation results is found in the calculation of rebar due to inaccuracies of 3D modeling carried out by engineers. 3D modeling on Revit software requires special skill for precision, accuracy, and expertise, as the potential for 3D modeling errors is very high.